PCBs in indoor air and human blood in Pittsfield, Massachusetts. (April 2022) - Casey, Ann; Bush, Brian; Carpenter, David O.
Abstract: Concentrations of polychlorinated biphenyls (PCBs) and three chlorinated pesticides were determined in serum from 21 residents of Pittsfield, MA and in the basement, living room and outdoor air of the 10 homes in which they lived. Median serum PCB levels were 4.2 ng/g, which are at least four times the average level in the US population, and consisted primarily of more highly chlorinated, persistent congeners. This reflects contamination with PCBs coming from the local General Electric facility. Median basement air concentration was 20.3 ng/m 3, while the median living room air was 11.4 ng/m 3 and median outdoor air concentration was 3.0 ng/m 3 . The PCB congeners detected in air were primarily low chlorinated (four and fewer) congeners, reflecting the greater volatility of PCBs with fewer chlorines. The congener pattern between basement and living room air showed a 95% correlation, while correlation with outdoor air was much less. While the congener pattern in air is very different from that of the PCB products used in Pittsfield (Aroclors 1254 and 1260), low chlorinated PCBs are detected in the vapor phase after air is blown across the commercial mixtures. The human serum samples did not show detectible levels of many of the congeners seen in the basement air samples, reflecting rapid metabolism of lower chlorinated PCBs by the human body. However, with continuous inhalation of indoor air, especially in the living room, the exposure to these non-persistent congeners may still have adverse health effects. Cellular studies of some of these non-persistent, low chlorinated congeners indicate that they are neurotoxic, mutagenic and cytotoxic. These results demonstrate the importance of consideration of inhalation of PCBs as a route of exposure, especially in indoor sites, and suggest that monitoring serum PCB concentration may not always provide a good measurement of exposure, especially to congeners that are relatively rapidly metabolized but have significant toxicity. Graphical abstract: Image 1 Highlights: Indoor PCB air levels were measured in homes in Pittsfield, Massachusetts. Blood samples of residents were obtained at the same time. Many lower chlorinated PCB congeners were in air but not in blood. Although these congeners are not persistent, they may have adverse health effects.